2023
DOI: 10.3389/fanim.2023.1111636
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the female reproductive tract microbiome and its relationship with the uterine environment for health and productivity in cattle: A review

Abstract: Once thought to be sterile, the reproductive tract microbiome has been characterized due to the transition from culture-dependent identification of bacteria to culture-independent sequencing methods. The urogenital microbiome was first identified in women through the Human Microbiome Project, which led to research in other species such as the bovine. Previous research focused on uterine bacteria associated with postpartum disease, but next generation sequencing methods identified a normal, healthy bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…There are studies in the female reproductive tract of cattle that showed variation by factors such as age, puberty, menstrual and estrous cycle 11 . In addition, samples were collected from different cows so we could have individual variation between samples and the correlation between UB and UH could be less clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies in the female reproductive tract of cattle that showed variation by factors such as age, puberty, menstrual and estrous cycle 11 . In addition, samples were collected from different cows so we could have individual variation between samples and the correlation between UB and UH could be less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies can use the knowledge of our results that can lead to other analyses related to reproductive features such as the success of embryonic implantation. Furthermore, these studies could consider variables such as estrous cycle, and puberty 11 . As we know, to achieve successful implantation, the uterus should undergo structural and functional remodeling 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, culture-independent high-throughput sequencing technologies have enabled the identification of commensal microbiota presence in the bovine uterus both during pregnancy and after parturition [100]. The potential role of the uterine microbiome in reproductive health, conception, and embryo development is increasingly appreciated [87,101,102]. Within the bovine uterine microbial community, methanogenic archaeal species have been reported.…”
Section: Methanogens In the Reproductive Tract: Vagina Uterus And Semenmentioning
confidence: 99%